2020
DOI: 10.1039/d0sc01229g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of thioethers, arenes and arylated benzoxazoles by transformation of the C(aryl)–C bond of aryl alcohols

Abstract: Transformation of aryl alcohols into high-value functionalized aromatic compounds by selective cleavage and functionalization of the C(aryl)-C(OH) bond is of crucial importance, but very challenging by far. Herein, for the first time, we report a novel and versatile strategy for activation and functionalization of C(aryl)-C(OH) bonds by the cooperation of oxygenation and decarboxylative functionalization. A diverse range of aryl alcohol substrates were employed as arylation reagents via the cleavage of C(aryl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Han et al. found that benzyl alcohols could be used as alternative arylation sources [301] . Under a similar Cu/Phen catalytic system, the alcohol substrate is in situ oxidized to the corresponding aromatic acid, which is the actual substrate of decarboxylative thioetherification reactions with diaryl disulfides.…”
Section: Decarboxylative C−chalcogen Bond Formationmentioning
confidence: 99%
“…Han et al. found that benzyl alcohols could be used as alternative arylation sources [301] . Under a similar Cu/Phen catalytic system, the alcohol substrate is in situ oxidized to the corresponding aromatic acid, which is the actual substrate of decarboxylative thioetherification reactions with diaryl disulfides.…”
Section: Decarboxylative C−chalcogen Bond Formationmentioning
confidence: 99%
“…Furthermore, we pioneered a novel, versatile approach involving oxygenation and decarboxylative functionalization for activating and functionalizing C aryl –C­(OH) bonds. A diverse range of aryl alcohol substrates underwent effective C aryl –C­(OH) bond activation, transforming into arene, thioether, and arylated benzoxazole products with remarkable yields with Cu-based catalysts …”
Section: Selective Bond Activation In Lignin Model Compoundsmentioning
confidence: 99%
“…103 Similar reaction conditions were applied to convert benzylic alcohols to thioethers via oxidative cleavage of the CAr-C(OH) bond and subsequent decarboxylation. 104 Other reported achievements include couplings of alkynyl carboxylic acids, 105 methylthiolations using DMSO, 106 and syntheses of perfluoroalkyl thioethers. 107…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…cleavage of the C Ar -C(OH) bond and subsequent decarboxylation. 104 Other reported achievements include couplings of alkynyl carboxylic acids, 105 methylthiolations using DMSO, 106 and syntheses of perfluoroalkyl thioethers. 107 Scheme 26 Cu-catalyzed decarboxylative coupling of benzoic acids 102 The approach towards thioethers via decarbonylation and decarboxylation is promising, also due to the availability of carboxylic acid derivatives.…”
Section: Review Synthesismentioning
confidence: 99%